2004
DOI: 10.1111/j.1471-4159.2004.02431.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide influences neurite outgrowth and neuroblastoma cell apoptosis regulated by novel protein kinase C isoforms

Abstract: We have previously seen that protein kinase C (PKC) e induces neurite outgrowth and that PKCd and PKCh elicit apoptosis in neuroblastoma cells. In this study we investigate the effects of cell-permeable C 2 -ceramide on these events in SK-N-BE(2) neuroblastoma cells. C 2 -ceramide abolishes neurite formation induced by overexpression of PKCe and, in cells overexpressing PKCd or PKCh, ceramide treatment leads to apoptosis. Exposure to C 2 -ceramide also suppressed neurite outgrowth induced by retinoic acid, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…9A). Treatment with TPA relocates the fusion protein to the plasma membrane, and, as reported previously (8,29), treatment with C 2 -ceramide induces a clear enrichment of ⑀FL in the perinuclear region. Combined treatment of C 2 -ceramide and TPA leads to a primarily cytoplasmic localization of ⑀FL-wt, which is analogous with studies on other cell types (8).…”
Section: Mutation Of the C1b Domain Makes Full-length Pkc⑀ Lesssupporting
confidence: 82%
See 1 more Smart Citation
“…9A). Treatment with TPA relocates the fusion protein to the plasma membrane, and, as reported previously (8,29), treatment with C 2 -ceramide induces a clear enrichment of ⑀FL in the perinuclear region. Combined treatment of C 2 -ceramide and TPA leads to a primarily cytoplasmic localization of ⑀FL-wt, which is analogous with studies on other cell types (8).…”
Section: Mutation Of the C1b Domain Makes Full-length Pkc⑀ Lesssupporting
confidence: 82%
“…We have previously shown that treatment with C 2 -ceramide induces a relocation of PKC⑀ to perinuclear structures that is accompanied by a suppression of the neurite-inducing capacity of PKC⑀ (29). The results in Fig.…”
Section: Mutation Of the C1b Domain Makes Full-length Pkc⑀ Lessmentioning
confidence: 62%
“…It is also possible that there are differences among these neurons in cellular targets for ceramide, which affect differentiation, proliferation, and cell death. It has been reported that the capacity of ceramide to induce apoptosis in SK-N-BE cells correlates with the expression levels of PKC-␦, which is a possible target of ceramide (Schultz and Larsson, 2004). Another intriguing possibility is that not only ceramide but also GlcCer affects the apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Silei et al, 2000;Fagerstrom et al, 1996), but there is still some controversy for the contribution of other nPKCs, namely PKC and . PKC , expressed occasionally in NB cells or tumors (Zeidman et al, 1999b), may contribute to apoptotic pathways in SK-N-BE(2) and SH-SY5Y cells (Schultz & Larsson, 2004;Schultz et al, 2003). Unlike , is commonly expressed (Zeidman et al, 1999b), yet again, transfection studies with full-length, catalytically inactive, or active PKC variants have revealed a pro-apoptotic role (Schultz et al, 2003;Schultz & Larsson, 2004).…”
Section: Aspects Of Pkc Regulation In Neuroblastoma Differentiation 2mentioning
confidence: 99%
“…PKC , expressed occasionally in NB cells or tumors (Zeidman et al, 1999b), may contribute to apoptotic pathways in SK-N-BE(2) and SH-SY5Y cells (Schultz & Larsson, 2004;Schultz et al, 2003). Unlike , is commonly expressed (Zeidman et al, 1999b), yet again, transfection studies with full-length, catalytically inactive, or active PKC variants have revealed a pro-apoptotic role (Schultz et al, 2003;Schultz & Larsson, 2004). A major role of PKC in the sensitization of NB cells (SH-SY5Y and SK-N-BE(2C)) to etoposide (Marengo et al, 2011) was just recently described, validating similar observations in other cell types (Griner and Katanietz, 2007).…”
Section: Aspects Of Pkc Regulation In Neuroblastoma Differentiation 2mentioning
confidence: 99%